Are There Enough Open Educational Resources Dealing With Social Science Research Methods? Insights From the D-A-CH Region - Prandner, Dimitri; Forstner, Matthias (Frontiers in Education, 2022)
The D-A-CH (Germany, Austria and Switzerland) region has traditionally been sceptical toward Open Educational Resources (OER) materials. Despite being strong partners for the open science community, the three German-speaking countries in Europe did not embrace wide-reaching OER policies in the past and offered only a limited number of incentives for supranational or nationwide genuine German language OER. These missing national initiatives can also be seen in the field of social science research-related materials. As the domain gained a lot of public interest during the COVID-19-pandemic, where attitudes, values and societal changes – traditionally the domain of social scientific inquiry – were spotlighted in the media and public discourse, it fell to individual universities, organizations and people to provide free online education materials – be they true OER or at least quasi-OER – that could help people within and outside of academia to understand and gain insight into the statistics and data presented and distributed via various channels. However, mapping the OER materials in this field during the summer of 2021 – one year after the pandemic had begun and the accompanying stream of data had started – revealed that the educational resources covering social science research methods that are offered in the German language are sparse, and those that are available are mostly quasi-OER, not fulfilling all the typical OER criteria. Thus, they have limited application scenarios. If the region wants to truly embrace an open science policy, it needs to strengthen OER in the future.